2008
DOI: 10.1016/j.bbr.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic modulation of reproductive behavior and activity in male zebra finches

Abstract: We previously demonstrated that hormone treatments which stimulate female-directed singing increased levels and turnover of dopamine (DA) in brain areas controlling the motor patterning of song. To help determine how DA affects singing, we quantified the effects of treating adult male finches with the D 1 /D 2 receptor antagonist cis-flupenthixol. Adult males were given subcutaneous silastic implants of androgen, in case drug treatment interfered with androgen secretion. One week later, they were tested with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
(67 reference statements)
1
24
1
Order By: Relevance
“…However, we here observed very close relationships between TH-Fos colocalization and courtship singing, and also between TH cell number and constitutive courtship motivation, as established through behavioral prescreenings. Considering that TH-ir neurons in the CG and VTA project directly to areas involved in singing and sexual motivation (16,17), and that DA promotes singing (8,28), our interpretations for courting males are fairly straightforward; the more DA neurons that a male exhibits in the CG and caudal VTA, and the greater their Fos activity, the greater the male's behavioral output. This interpretation is likewise consistent with the fact that non-courters express low levels of colocalization after exposure to female.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we here observed very close relationships between TH-Fos colocalization and courtship singing, and also between TH cell number and constitutive courtship motivation, as established through behavioral prescreenings. Considering that TH-ir neurons in the CG and VTA project directly to areas involved in singing and sexual motivation (16,17), and that DA promotes singing (8,28), our interpretations for courting males are fairly straightforward; the more DA neurons that a male exhibits in the CG and caudal VTA, and the greater their Fos activity, the greater the male's behavioral output. This interpretation is likewise consistent with the fact that non-courters express low levels of colocalization after exposure to female.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings demonstrate that DA signals derived from the VTA-substantia nigra pars compacta complex are essential for the context-dependent modulation of song in the zebra finch (6,36), and various other findings likewise show that DA is important for the regulation of song (8,28,37). However, previous experiments have found that singing is correlated with immediate early gene expression only within nondopaminergic neurons of the VTA (6,32), although those studies appear to have focused predominantly on the rostral portion of the VTA.…”
Section: Da Neurons Of the Cg Are Strongly Coupled To Song And Reflectmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional data from pharmacological manipulations in zebra finches support a role for DA in stimulating directed vocal communication [24]. Because these drugs were administered systemically, it is impossible to discern where in the brain altered dopaminergic function influences sexually motivated vocal communication.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that within a breeding context, peripheral injections of DA agonists stimulate whereas DA antagonists inhibit song produced by male starlings in response to the introduction of a female [23]. In male zebra finches, DA antagonists also inhibit courtship singing [24] and in vivo microdialysis reveals that levels of DA in the avian basal ganglia (Area X) are elevated during song that is directed towards a conspecific [25]. A role for DA in the regulation of goal-directed vocal behavior extends beyond songbird model systems.…”
Section: Introductionmentioning
confidence: 95%